(untitled) (Journal of Oriental Studies, 2025)
This article explores the transmission and transformation of medical knowledge in the Ottoman Empire through selected Armeno-Turkish manuscripts from the 18th to the 19th centuries. It highlights the European influence on Ottoman medicine via Latin and Arabic texts, which were translated into Turkish and Armenian scripts, reflecting a dynamic process of localization and adaptation. The study focuses on four significant manuscripts housed at the Matenadaran, illustrating diverse sources—from Arabic, Latin (Italian) —to demonstrate how medical terminology, practices, and cultural exchanges shaped regional medical traditions. The involvement of religious institutions, particularly the Armenian Church and Protestant communities, played a critical role in knowledge dissemination, fostering cross-cultural interactions and linguistic enrichment. The manuscripts reveal early 19th-century efforts to incorporate modern European medical ideas into Ottoman society, emphasizing the importance of translation and contextualization in medical education. Ultimately, these handwritten texts serve as valuable cultural artifacts, highlighting the complex interplay between traditional and modern medicine, local needs, and external influences in shaping Ottoman medical history.